The Story of Art - Ernst Hans Gombrich 1909-2001 (UK Phaidon Press Limited, 1995)
"The Story of Art is one of the most famous and popular books on art ever published. For 45 years it has remained unrivalled as an introduction to the whole subject, from the earliest cave paintings to the experimental art of today. Readers of all ages and backgrounds throughout the world have found in Professor Gombrich a true master, who combines knowledge and wisdom with a unique gift for communicating directly his own deep love of the works of art he describes." "The Story of Art owes its lasting popularity to the directness and simplicity of the writing, and also the author's skill in presenting a clear narrative. He describes his aim as 'to bring some intelligible order into the wealth of names, periods and styles which crowd the pages of more ambitious works', and using his insight into the psychology of the visual arts, he makes us see the history of art as 'a continuous weaving and changing of traditions in which each work refers to the past and points to the future', 'a living chain that still links our own time with the Pyramid age'. In its new format, the 16th edition of this classic work is set to continue its triumphant progress for future generations and to remain the first choice for all newcomers to art."--Jacket
Introduction: On arts and artists -- Strange beginnings : prehistoric and primitive peoples; Ancient America -- Art for eternity : Egypt, Mesopotamia, Crete -- The great awakening : Greece, seventh to fifth century BC -- The realm of beauty : Greece and the Greek world, fourth century BC to first century AD -- World conquerors : Romans, Buddhists, Jews and Christians, first to fourth century AD -- A parting of ways : Rome and Byzantium, fifth to thirteenth century -- Looking eastwards : Islam, China, second to thirteenth century -- Western art in the melting pot : Europe, sixth to eleventh century -- The church militant : the twelfth century -- The church triumphant : the thirteenth century -- Courtiers and burghers : the fourteenth century -- The conquest of reality : the early fifteenth century -- Tradition and innovation I : the later fifteenth century in Italy -- Traditions and innovation II : the fifteenth century in the North -- Harmony attained : Tuscany and Rome, early sixteenth century -- Light and colour : Venice and northern Italy, early sixteenth century -- The new learning spreads : Germany and the Netherlands, early sixteenth century -- A crisis of art : Europe, later sixteenth century -- Vision and visions : Catholic Europe, first half of the seventeenth century -- The mirror of nature : Holland, seventeenth century -- Power and glory I : Italy, later seventeenth and eighteenth centuries -- Power and glory II : France, Germany and Austria, late seventeenth and early eighteenth centuries -- The age of reason : England and France, eighteenth century -- The break in tradition : England, America and France, late eighteenth and early nineteenth centuries -- Permanent revolution : the nineteenth century -- In search of new standards : the late nineteenth century -- Experimental art : the first half of the twentieth century -- A story without end: The triumph of modernism ; Another turning of the tide ; The changing past
Keywords: Arts (3Gdafs; Art -- History; Arte -- Historia; Art, General; General